The Effect of the Rock Slope Material on the Compressive Strength Value in Malino, South Sulawesi Province: Pengaruh Material Penyusun Lereng Batuan terhadap Nilai Kuat Tekan di Daerah Malino Provinsi Sulawesi Selatan - Dian Dwi Apriliyani Arsdin; Purwanto Purwanto; Muhammad Ramli (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2022)
The research location is on the upstream slope of the Jeneberang River in Malino, Gowa Regency, South Sulawesi. This study aims to determine the types of rocks the slopes and to study the relationship between mineralogy characteristics and rock mechanical properties. Mineralogical characteristics analysis used petrographic analysis, XRD and XRF, while for the analysis of rock mechanical properties using uniaxial compressive strength analysis in this study used three types of samples taken on the same slope with the top, middle and bottom sampling points. The results of this study indicate that the rock types found on the slopes are andesite igneous rock types with the same main mineral types, the mineral is albit, analcime, quartz and leucite, while the secondary minerals found in each sample are different, on the slopes of sample A the secondary mineral is spodumene, sample B secondary mineral is garnet and sample C is palygorskite. The value of the results of testing the mechanical properties of each sample is also different, the correlation of the three uniaxial compressive strength test values to the mineral composition of rock samples shows that the correlation of quartz minerals to the compressive strength value and young's modulus has a fairly high correlation value of 0,934 and 0,9798, the mineral correlation value to the poisson ratio indicates that the mineral leucite has high correlation value compared to other minerals.